Impact of AI Dependence on Procrastination among University Students - Maliha Mukhtar; Syeda Sajida Firdos; Iram Zaka; Saira Naeem (Research Journal of Psychology, 2025)
This study investigated the impact of AI dependence on procrastination among university students by contributing to the understanding of over reliance on AI and its outcome as procrastination. The sample of the study was comprised of (N=113) university students, aged between 18 and 35 from various academic disciplines and universities Multan. Cross-sectional, quantitative methods were utilized, along with the convenient sampling technique. Data was collected through google forms. A self-structured demographic sheet along with the two scales was used in this study. Dependence on Artificial Intelligence Scale (DAI) (Morales-García et al., 2024), evaluated the extent of dependence that university students exhibit towards artificial intelligence. The Tuckman Procrastination Scale (TPS) (Tuckman, 1991), measured the level of procrastination among students. Results revealed that AI dependence is positively correlated (r=.241*), and predicts (p=.010*) the procrastination. This overreliance on AI results in higher tendency of procrastination among students. However, no significant difference was found in level of education and area of residence regarding AI dependence and procrastination among university students.